Built environment for memorisation: enhancing the hafazan performances through learning spatial quality and sitting styles - Ab Jalil, Nurlelawati; Ab. Jalil, Habibah; Salleh, Nurul Hamiruddin; Ibrahim, Mohamad Nordin; Ghozali, Salahuddin; Mohammed Abdul Rahman, Mohamad Rahim (2020)
Past studies have reiterated that environmental quality is the key to better education. A well-defined learning environment is not only promoting a better learning engagement and emotional impact. It also contributes to students’ positive perception of their ability to succeed. The need for the improvement should be extended to all education streams, including the quality of the Islamic education institutions. This paper aimed to explore whether the students’ learning environment and the sitting facilities play an important role in achieving better performance. The objectives of the study were to: (i) analyse the effect of the learning environment on the performance of tahfiz students between gender in Quran memorisation and (ii) investigate the impact of students’ sitting style towards their Quran memorisation performance. A total of 24 tahfiz students were selected to participate in the 10-day experiment. In knowing their perception in each sitting, each student was required to complete a different hafazan task in various positions provided during the experiment. The findings showed that the male students were affected more emotionally and performance when they sat on a chair as compared to sitting cross-legged. Conversely, female students claimed both sitting styles had similar effects in terms of condition, which caused sleepiness, sickness and delays throughout the experiment. Concisely, both gender seemed to have better performance when they sat cross-legged, regardless of their perceptions towards the sitting condition. The findings propose that these could be due to their common sitting style (cross-legged) practices and adapted before the experiment. This research can be a turning point in improving the quality of Tahfiz learning premises for better learning experience and performance.